LYVE-1, the lymphatic system and tumor lymphangiogenesis - Jackson, David G; Prevo, Remko; Clasper, Steven; Banerji, Suneale (Trends in immunology, 2001)
Previous research into hyaluronan (HA) has focused on the role of this abundant tissue glycosaminoglycan in promoting cell migration through interactions with its transmembrane receptor CD44 on inflammatory leukocytes and tumor cells. The recent discovery of a new HA receptor, LYVE-1 (lymphatic vessel endothelial HA receptor), expressed predominantly in lymphatic vessels, highlights another aspect of HA biology: its continuous transit through the lymphatic system and its potential involvement in lymph node homing by CD44 + leukocytes and tumor cells. The functional role of LYVE-1 in lymphatic vessels and its application as a marker to study tumor lymphangiogenesis are important areas of investigation.